Enhanced Caenorhabditis elegans locomotion in a structured microfluidic environment. - Sungsu Park (Public Library of Science (PLoS), 2008)
Background Behavioral studies of Caenorhabditis elegans traditionally are done on the smooth surface of agar plates, but the natural habitat of C. elegans and other nematodes is the soil, a complex and structured environment. In order to investigate how worms move in such environments, we have developed a technique to study C. elegans locomotion in microstructures fabricated from agar. Methodology/principal findings When placed in open, liquid-filled, microfluidic chambers containing a square array of posts, we discovered that worms are capable of a novel mode of locomotion, which combines the fast gait of swimming with the more efficient movements of crawling. When the wavelength of the worms matched the periodicity of the post array, the microstructure directed the swimming and increased the speed of C. elegans ten-fold. We found that mutants defective in mechanosensation (mec-4, mec-10) or mutants with abnormal waveforms (unc-29) did not perform this enhanced locomotion and moved much more slowly than wild-type worms in the microstructure. Conclusion/significance These results show that the microstructure can be used as a behavioral screen for mechanosensory and uncoordinated mutants. It is likely that worms use mechanosensation in the movement and navigation through heterogeneous environments.